The Supply Chain Quality Management in High Education: A Case Study in Indonesia - Indrianawati Usman (International Journal of Supply Chain Management, 2020)
Abstract- The purpose of this research is to formulate the supply chain quality management model by identifying the importance factors which contribute the success of supply chain quality management practice in the operational academic process. Reseach design: This research is exploratory in nature using case study in the supply chain member of study program academic process. The approach is by identifying the framework parameter of supply chain quality management. Focus of study is cross sectional to the member of study program’s supply chain which includes new student admissions centers, head of study program, quality assurance centers and career development centers. The information collected by in depth interview and analyzed data from academic process business document. Data analysis is done by open coding, axial coding, and selective coding, indentifying relevant concepts and classifying them into several categories. Result of this paper is the identification of the key elements that support the success of academic business process of study program in implementing supply chain quality management and presenting the supply chain quaity management model implementation, support by the essential elements found. Research Contributio: This research present the importance input for the concept regarding the integration of total quality management and supply chain management implementation of study program’s operationa academic process in high education. This study compiling the development of the concept of supply chain quality management implementation concept and proposition in the form of a causal model that links the influence between several related concepts in supply chain quality management. The results of this study is also valuable for other service industry especially services which have strong involvement between client and server.